Effects of sleep on a high-heat capacity mattress on sleep stages, EEG power spectra, cardiac interbeat intervals and body temperatures in healthy middle-aged men. Issue 5 (4th November 2019) - Herberger, Sebastian; Kräuchi, Kurt; Glos, Martin; Lederer, Katharina; Assmus, Lisa; Hein, Julia; Penzel, Thomas; Fietze, Ingo
Abstract: Study Objectives: This study deals with the question whether a slow (non-disturbing) reduction of core body temperature (CBT) during sleep increases sleep stage N3 and EEG slow wave energy (SWE) and leads to a slowing of heart rate in humans. Participants: Thirty-two healthy male subjects with a mean ± SD age 46 ± 4 years and body mass index 25.2 ± 1.8 kg/m 2 . Methods: A high-heat capacity mattress (HM) was used to lower body temperatures in sleep and was compared to a conventional low-heat capacity mattress (LM) in a double-blinded fashion. Polysomnography was performed accompanied by measurements of skin-, core body- and mattress surface-temperatures, and heart rate. EEG power spectral analyses were carried out using Fast Fourier Transform. Interbeat intervals were derived from the electrocardiogram. Results: The HM led to a larger decline in CBT, mediated through higher heat conduction from the core via the proximal back skin onto the mattress together with reduced heart rate. These effects occurred together with a significant increase in sleep stage N3 and standardized slow wave energy (sSWE, 0.791–4.297 Hz) accumulated in NREM sleep. In the 2nd half of the night sSWE increase was significantly correlated with body temperature changes, for example with CBT decline in the same phase. Conclusions: A HM subtly decreases CBT, leading to an increased amount of sleep stage N3 and of sSWE, as well as a slowing of heart rate.